2011
DOI: 10.1007/s10452-011-9383-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fatty acids and elemental nutrients in periphyton, invertebrates, and cutthroat trout (Oncorhynchus clarki) in conifer and alder streams of western Washington state

Abstract: Organism growth and reproduction are often limited by nutrient availability in freshwater ecosystems where, in some cases, food webs are primarily supported by allochthonous organic matter. Therefore, we hypothesized that the composition of riparian vegetation would influence the variability of N, P, and fatty acid content of in-stream consumers. Specifically, we predicted that organisms living in alder streams would have higher levels of N, P, and polyunsaturated fatty acids than organisms in coniferous strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Terrestrial vegetation, particularly grasses and herbaceous plants, had high ALA, in line with results for trees from diverse biomes (mangroves [Carreon-Palau et al 2013], alder and hemlock [Volk and Kiffney 2012]). Terrestrial vegetation, particularly grasses and herbaceous plants, had high ALA, in line with results for trees from diverse biomes (mangroves [Carreon-Palau et al 2013], alder and hemlock [Volk and Kiffney 2012]).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Terrestrial vegetation, particularly grasses and herbaceous plants, had high ALA, in line with results for trees from diverse biomes (mangroves [Carreon-Palau et al 2013], alder and hemlock [Volk and Kiffney 2012]). Terrestrial vegetation, particularly grasses and herbaceous plants, had high ALA, in line with results for trees from diverse biomes (mangroves [Carreon-Palau et al 2013], alder and hemlock [Volk and Kiffney 2012]).…”
Section: Discussionsupporting
confidence: 84%
“…Though terrestrial sources did not contain C20 and C22 PUFA, they had high contents of C18 PUFA (ALA and LIN), the precursors for C20 and C22 PUFA synthesis. Terrestrial vegetation, particularly grasses and herbaceous plants, had high ALA, in line with results for trees from diverse biomes (mangroves [Carreon-Palau et al 2013], alder and hemlock [Volk and Kiffney 2012]). Highly processed terrestrial material tends to be lower in ALA (Torres-Ruiz et al 2007), much like we observed for leaf litter.…”
Section: Discussionsupporting
confidence: 84%
“…Fatty acid profiles readily distinguished between biofilm, invertebrates, and Atlantic salmon parr at all sampling periods, a result also found in other studies involving salmonids (e.g., Heintz et al. , Volk and Kiffney ). The variability in FA profiles was accredited to inherent differences between trophic groups combined with assimilation of marine‐derived FAs in the MDN treatments.…”
Section: Discussionsupporting
confidence: 86%
“…Our study was conducted in early summer in subtropical areas with the stream temperature range 17–25 °C, thus SAFA% appeared to be higher and PUFA% lower. A field investigation in six headwater streams in western Washington State (Volk & Kiffney, ) with a 7‐day average temperature of 11.5–12 °C, showed a similar proportion of periphyton SAFA (48%) to our results, but PUFA (28%) were lower than the artificial stream study (Hill et al ., ). These differences confirm that periphyton FA compositions are influenced by the interplay of several different environmental factors.…”
Section: Discussionmentioning
confidence: 99%